Optical Reflection-Intensity-Distribution Reproduction Based on the Detection of Interference Spectrum Distribution -A Direct Detection Method - ANDOU, Naoki; ICHIMURA, Tsutomu; ENDOU, Shigeru; ODAGIRI, Yoshiki; TAN-NO, Naohiro; FUNABA, Tadayuki (Rēzā kenkyū, 1996)
We propose and confirm a novel techniqe of optical frequency domain reflectometry based on the detecton of an interference spectrum by using a multi-mode laser. The proposed systems composed of a free-running laser diode, an optical spectrometer and a computing system for FFT can easily provide the potential for ultrahigh resolution on the order of 10 μm without scanning frequencies as in frequency domein refletometers of either the continuously or the stepwise-swept variety.